2020
DOI: 10.3389/fphar.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

Treating Different Diseases With the Same Method—A Traditional Chinese Medicine Concept Analyzed for Its Biological Basis

Abstract: Introduction The fundamental theory of traditional Chinese medicine (TCM) implies that when different diseases have the same pathogen, the syndromes of these individual diseases will be the same. “Treating different diseases with the same method” is a TCM principle suggesting that when different diseases have similar pathological changes during different stages of their development, the same method of treatment can be applied. Our study aims to analyze the concept “treating different diseases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Using a systems biology approach with the combination of computational analysis and animal experiment, Li et al [ 46 ] have found that “Cold ZHENG” and “Hot ZHENG” have their own corresponding genetic pathways. Zhai et al [ 47 ] found that 46 genes were involved in the Qi deficiency and blood stasis syndrome of both stroke and coronary heart disease (CHD) by means of data mining, which also supported the existence of biological basis under TCM syndrome (“ZHENG” in Chinese). In our study, as mentioned before, the symptoms in M3 have corresponding syndrome LYHS and prescriptions in the theory of TCM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using a systems biology approach with the combination of computational analysis and animal experiment, Li et al [ 46 ] have found that “Cold ZHENG” and “Hot ZHENG” have their own corresponding genetic pathways. Zhai et al [ 47 ] found that 46 genes were involved in the Qi deficiency and blood stasis syndrome of both stroke and coronary heart disease (CHD) by means of data mining, which also supported the existence of biological basis under TCM syndrome (“ZHENG” in Chinese). In our study, as mentioned before, the symptoms in M3 have corresponding syndrome LYHS and prescriptions in the theory of TCM.…”
Section: Discussionmentioning
confidence: 95%
“…Using a systems biology approach with the combination of computational analysis and animal experiment, Li et al [46] have found that "Cold ZHENG" and "Hot ZHENG" have their own corresponding genetic pathways. Zhai et al [47] found 8…”
Section: Discussionmentioning
confidence: 99%
“…According to the TCM theory, SGD (xerostomia and dysphagia) are caused by heat toxins, and the methods used to treat SGD are roughly the same. This concept is called "Yi Bing Tong Zhi" (same treatment for the same syndrome with different diseases) (Zhai et al, 2020). However, from the perspective of modern medicine, especially the scientific research design, although most of these tumors belong to squamous cell carcinoma, their pathogenesis is different.…”
Section: Tumor Typesmentioning
confidence: 99%
“…In Chinese Medicine (CM) theory, multiple diseases in different people may be treated in the same manner ( Zhai et al, 2020 ). Under this treatment principle, the same strategy is used to treat patients with multiple diseases who have the same syndrome (Zheng) ( Jiang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have adopted the concept of innovative basket trial design beyond the field of cancer research and have now developed a Phase II herbal trial protocol for treatment of patients with ischemic stroke, stable angina pectoris, and diabetic peripheral neuropathy, who share the same syndrome target [Qi deficiency and blood stasis (QDBS) syndrome] for herbal therapy. QDBS syndrome is one of the basic CM syndromes that is most strongly related to various diseases, including vascular, cardiovascular, and cerebrovascular diseases, and guides the use of herbal medicine ( Zhai et al, 2020 ). It is a common and core pathogenesis of multiple diseases ( Li et al, 2007 ), with a cluster of symptoms, including fatigue, shortness of breath, reticence to speak, spontaneous sweating, pale or dark complexion, local stabbing pain, pale purple tongue, or pale dark tongue.…”
Section: Introductionmentioning
confidence: 99%